Types of Medicinal Plants in Ombo Village, Sirenja Sub-District and Their Use as Learning Media - Radifa zahra; Lestari M.P. Alibasyah; Lilies N. Tangge (Equator Science Journal, 2024)
The purpose of this research is to describe the types of medicinal plants, parts of medicinal plants and the processing of medicinal plants and to produce learning media in the form of pocket books. This research was carried out in January-July 2024 in Ombo Village, Sirenja District. This type of research is in the form of descriptive qualitative research with data collection techniques of Observation, interviews, surveys and documentation and using the purposive sampling method. The results of the research obtained are 28 species of medicinal plants. Processing by boiling is the most, which is as many as 16 species, in addition to the processing by grinding and pounding and boiling. The leaves are the most widely used, namely 18 species, besides that the parts used are also the stems, fruits, rhizomes and roots. The results of the research on the types of medicinal plants in Ombo Village, Sirenja District, are very feasible to be used as a learning medium with an average score of 82.64%.